Respuesta :

Answer:

x = -4; y = -3

Step-by-step explanation:

2x - 5y = 7

3x - y = -9

Rewrite top equation. Multiply both sides of bottom equation by -5. Add equations. This eliminates y, and we solve for x.

         2x - 5y = 7

(+)   -15x + 5y = 45

----------------------------

      -13x         = 52

Divide both sides by -13.

x = -4

Substitute -4 for x in the first original equation and solve for y.

2x - 5y = 7

2(-4) - 5y = 7

-8 - 5y = 7

-5y = 15

y = -3

Answer: x = -4; y = -3

-5 =

ACCESS MORE